A Survey of Different Barrier layers and Indium Content of InGaAs MOSFETs - .Rajakumari, R; Parveen, A.Sakira (IJRDO-Journal of Applied Science, 2018)
A barrier layer in an InGaAs MOSFET, whichshows promise for high-performance logic applications due toenhanced electron mobility, is known to further improve theelectron mobility. In this paper, a detailed investigation of theimpact of different barrier layers on the analog performance of anInGaAs MOSFET is reported for the first time. The deviceparameters for analog applications, such as transconductance (gm), transconductance-to-drive current ratio (gm /IDS), drainconductance (gd ), intrinsic gain (gm /gd ), and unity-gain cutofffrequency (f T ) are studied with the help of a device simulator. Abarrier layer is found to improve the analog performance of sucha device in general; with a double-barrier layer showing the bestperformance. An investigation on the impact of varying theindium content in the channel on the analog performance of anInGaAs MOSFET with a double-barrier layer is also reported inthis paper. It is found that a higher In content results in betteranalog performance of such devices.